Somatotype and body composition of volleyball players and untrained female students – reference group for comparison in sport - Pastuszak, Anna; Buśko, Krzysztof; Kalka, Ewa (Anthropological Review, 2016)
There is substantial evidence that somatotype and success in sport and physical performance are positively related. Existing somatotype data on athletes are useful as guidelines for sport selection and choice of training appropriate to the enhancement of desired somatotype characteristics. Updated somatotype data from non-athlete reference groups complement comparative analysis applied in assessing the effects of the training process and selection. The aim of this study was to determine the somatotype of untrained girls studying at Warsaw University of Technology in 2011, in order to create a current reference group for comparison, and to investigate the difference in body build of female volleyball players compared with the non-athlete group. Twelve Second Division female volleyball players (age 21.6±1.5 years, body height 177.3±6.2 cm, body mass 71.0±6.5 kg, training experience 8.4±3.4 years) and 150 female untrained students of the University of Technology in Warsaw (age 20.0±6.4 years, body height 166.5±6.4 cm, body mass 59.7±8.4 kg) participated in a study carried out in 2011. Somatotype was determined using the Heath-Carter method. The volleyball players were a little older and were significantly taller and heavier than female students (p<0.05). Significant differences between the groups were found in breadth of the elbow, breadth of the wrist, biacromial diameter, arm circumference and crus circumference (p<0.05). The mean somatotype of the volleyball players was 4.5-3.4-2.8. (4.5±1.0-3.4±1.2-2.8±1.3), whilst that of the untrained students was 5.1-3.6-2.8. (5.1±1.4-3.6±1.1-2.8±1.3); the groups did not differ significantly in somatotype. The groups were significantly different in body composition (F [kg] and LBM [kg]), as estimated by BIA and anthropometric methods (p<0.05). No differences were observed between the groups in the skinfolds. Morphological characteristics of the female volleyball players depended on the competition level and performance. Somatic features of the bodies of the volleyball players were dominated by the height of the body and the associated magnitude of the constituent characteristics.